Small matters : Canadian children in sickness and health, 1900-1940 - Gleason, Mona, 1964- (McGill-Queen's/Associated Medical Services studies in the history of medicine, health, and society, 2013)
What was it like to be young and sick in the past? Who taught children how to be healthy and what were they expected to learn? In Small Matters, Mona Gleason explores how medical professionals, lay practitioners, and parents understood young patients and how children responded. During the first half of the twentieth century, particularly in the interwar decades, a number of changes took shape within the field of child healthcare - the rise of pediatrics as a medical profession, efforts to ameliorate maternal and infant mortality rates, and the shift of focus from controlling contagious diseases to the prevention of illness. Gleason makes use of oral histories throughout this period of health and welfare reform to shed new light on children's attitudes toward their medical treatment, their largely unexplored experiences of hospitalization and disability, and the importance of teachers and health curriculum to the development of "healthy habits." By focusing on children's medical treatment beyond the doctor's office, and by paying particular attention to the experience of marginalized children, Gleason makes a major contribution to the history of Canadian childhood and healthcare. The first work of its kind, Small Matters explores how children faced death, endured illness, and learned to be healthy in the context of their families and communities.